Codes of teenage characters and mama in their talks portraying the sociolinguistic features - Ajar Pradika Ananta Tur; Shella Antoro Putri (University of Muhammadiyah Purwokerto, 2020)
Code switching and code mixing have become a trend in teenagers’ communication today. Not only in communicating, code switching and code mixing also influence the author’s style in writing novels. However, recently, it is not easy to define which is code switching or code mixing because the occurrence of the codes is very tight recently. The characters in the novel often do codes at least Indonesian-English. The objectives of this study are to find out the form of codes and the sociolinguistic features of the characters in Refrain novel. This research uses descriptive qualitative design from collecting the data until analyzing them. The result of the analysis yields some forms of codes spoken by the characters in the novel. The forms are sentence, clause, phrases like noun phrase & verb phrase, and words like noun, verb, adjective, & adverb. The other problem indicating their social background reflects the sociolinguistic features of the characters. They are education, family, friendship, and occupation.